Basics of Group Behavior and Teamwork Understanding at Az Zahra Islamic Elementary School Bandar Lampung - Dahlia, Hernis; Ghoni, Miftahul; Siamanto, Latif; Hadiati, Eti (Journal of Advanced Islamic Educational Management, 2025)
In education, especially at the primary level, successful learning is not only determined by individual factors but also by social interaction and cooperation between group members. Therefore, in-depth research on group behavior and effective teamwork is very important to create a conducive and productive learning environment. This research aims to explore the basics of group behavior and teamwork at SD Islam Az Zahra Bandar Lampung, especially in the context of learning and school management. More specifically, analyzing the dynamics of group behavior among students, identifying factors that influence group behavior in schools, knowing how the role of teamwork among teachers and staff at SD Islam Az Zahra, and analyzing leadership and its influence on teamwork. Through this research it is hoped that continuous improvement can be found to improve the quality of education in schools. This research used a descriptive qualitative approach with a case study method. Data were collected through in-depth interviews, direct observation and documentation related to group activities and teamwork at school. In the world of education, especially at the primary level, the success of learning t The data obtained were analyzed using data reduction techniques, data presentation, and conclusion drawing to provide a deeper understanding of the dynamics that occur at Az Zahra Islamic Elementary School. The results show that the dynamics of group behavior among students are quite active, although there are challenges related to differences in academic and social abilities that affect group interactions. Teachers play an important role in managing student groups by setting norms and rules that support cooperation. On the other hand, teamwork between teachers and administrative staff in the school also works well, although there are sometimes differences in views regarding teaching methods and division of tasks. Principals with transformational leadership styles play an important role in promoting more effective collaboration among team members, which in turn supports the achievement of educational goals in the school.